Meta-analysis of the effects of on-farm management strategies on milk yields of dairy cattle on smallholder farms in the Tropics - Bateki, Christian A; Dijk, Suzanne van der; Wilkes, Andreas; Dickhöfer, Uta; White, Robin (Elsevier, 2020)
Although East Africa is home to one of the most advanced dairy industries in Sub-Saharan Africa, regional annual milkproduction is insufficient to meet the demand. The challenge of increasing milk yields (MYs) among smallholder dairy cattlefarmers (SDCFs) has received considerable attention and resulted in the introduction of various dairy management strategies(DMSs). Despite adoption of these DMSs, MYs remain low on-farm and there is a large discrepancy in the efficacy of DMSsacross different farms. Therefore, the present study sought to: (1) identify on-farm DMSs employed by East African SDCFs toincrease MYs and (2) summarize existing literature to quantify the expected MY changes associated with these identified DMSs.Data were collected through a comprehensive literature review and in-depth semi-structured interviews with 10 experts from theEast African dairy sector. Meta-analysis of the literature review data was performed by deriving four multivariate regressionmodels (i.e. models 1 to 4) that related DMSs to expected MYs. Each model differed in the weighting strategy used (e.g. numberof observations and inverse of the standard errors) and the preferred model was selected based on the root estimated errorvariance and concordance correlation coefficient. Nine DMSs were identified, of which only adoption of improved cattle breedsand improved feeding (i.e. increasing diet quality and quantity) consistently and significantly (P<0.05) increased daily MYsacross the available studies. Improved breeds alongside adequate feeding explained≤50% of the daily MYs observed in themetadata while improved feeding explained≤30% of the daily MYs observed across the different models. Conversely, calfsuckling significantly (P<0.05) reduced MYs according to model 2. Other variables including days in milk, trial length andmaximum ambient temperature (used as a proxy for heat stress) contributed significantly to decreasing MYs. These variables mayexplain some of the heterogeneity in MY responses to DMSs reported in the literature. Our results suggest that using improvedcattle breeds alongside improved feeding is the most reliable strategy to increase MYs on-farm in East Africa. Nevertheless, theseDMSs should not be considered as standalone solutions but as a pool of options that should be combined depending on theresources available to the farmer to achieve a balance between using dairy cattle genetics, proper husbandry and feeding tosecure higher MYs.